2015
DOI: 10.4103/0366-6999.170260
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine-midazolam versus Sufentanil-midazolam for Awake Fiberoptic Nasotracheal Intubation

Abstract: Background:Awake fiberoptic intubation (AFOI) is usually performed in the management of the predicted difficult airway. The aim of this study was to evaluate the feasibility of dexmedetomidine with midazolam (DM) and sufentanil with midazolam (SM) for sedation for awake fiberoptic nasotracheal intubation.Methods:Fifty patients with limited mouth opening scheduled for AFOI were randomly assigned to two groups (n = 25 per group) by a computer-generated randomization schedule. All subjects received midazolam 0.02… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 24 publications
3
33
0
Order By: Relevance
“…In this study, the results were found to be comparable for the two groups in terms of patients' tolerance and intubating conditions without affecting the patency of the upper airway. However, it has proved to be important to keep patients of sufentanil group responsive and compliant for the potential risk of respiratory depression [43]. Compared with placebo, in a multicenter study, Bergese et al evaluated the safety and efficacy of DEX for Sedation During AFOI, showing that considerably less DEX patients than placebo patients needed midazolam to obtain and sustain the required sedation.…”
Section: Use Of Dexmedetomidine In Afoimentioning
confidence: 99%
“…In this study, the results were found to be comparable for the two groups in terms of patients' tolerance and intubating conditions without affecting the patency of the upper airway. However, it has proved to be important to keep patients of sufentanil group responsive and compliant for the potential risk of respiratory depression [43]. Compared with placebo, in a multicenter study, Bergese et al evaluated the safety and efficacy of DEX for Sedation During AFOI, showing that considerably less DEX patients than placebo patients needed midazolam to obtain and sustain the required sedation.…”
Section: Use Of Dexmedetomidine In Afoimentioning
confidence: 99%
“…It can induce a 'wakable' state that is similar to normal sleep. There are many studies on the use of dexmedetomidine in awake fiberoptic bronchoscopy intubation (AFOBI) [7]. A recent review reported that dexmedetomidine can cause fewer desaturation episodes than propofol and opioids when used in AFOBI [8].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, when used as an adjuvant for induction of anesthesia, dexmedetomidine improves hemodynamic stability by decreasing the hemodynamic changes caused by endotracheal intubation [14]. Furthermore, dexmedetomidine is known to have sedative and airway reflex blunting effects, providing better conditions for awake fiberoptic intubation, awake blind nasotracheal intubation, and laryngeal mask airway placement when used with propofol [15][16][17].…”
Section: Introductionmentioning
confidence: 99%